Dynamic brain-heart interaction in sleep characterized by variational phase-amplitude coupling framework - Juntong Lyu; Chien-Hung Yeh; Wenbin Shi; Thomas Penzel (Communications Biology)
Abstract Sleep is a complex physiological state characterized by synchronized cortical and cardiac oscillations, which reflect dynamic communication and interaction between the central (CNS) and autonomic (ANS) nervous systems, crucial for maintaining homeostasis and overall health. However, the dynamic interplay between CNS and ANS rhythmicities in sleep remains unclear. Here, we present a variational phase-amplitude coupling framework that associates frequency modulations of the electroencephalogram and cardiac R-peak intervals across sleep dynamics. We validate the robustness of our method on spurious couplings by nonlinear or nonstationary simulations. Moreover, delta-range slow cortical oscillations exhibit robust coupling with both the low- (HRV-LF) and high-frequency (HRV-HF) constituents of RR-interval heart-rate variability, thereby constituting a cardinal electrophysiological signature of ANS-CNS modulation. Furthermore, we highlight the significance of the “decoupling phenomenon” in a transitional period from wake to sleep for sleep preparation, and discover stronger couplings between the HRV-LF component and EEG-δ wave, and weaker couplings between the HRV-HF component and EEG-δ activity for obstructive sleep apnea (OSA) patients compared to healthy individuals, and finally uncover the key patterns of brain-heart interaction in both healthy cohorts and OSA patients during sleep.